Sarcopenia Is Associated With a Risk of Mortality in People With Type 2 Diabetes Mellitus - Takahashi, Fuyuko; Hashimoto, Yoshitaka; Kaji, Ayumi; Sakai, Ryosuke; Okamura, Takuro; Kitagawa, Noriyuki; Okada, Hiroshi; Nakanishi, Naoko; Majima, Saori; Senmaru, Takafumi; Ushigome, Emi; Hamaguchi, Masahide; et al. (Frontiers in Endocrinology, 2021)
Background: Sarcopenia has reportedly been associated with increased risk of mortality in general populations. However, few studies have investigated the association between sarcopenia and mortality in older people with type 2 diabetes mellitus (T2D). This study aimed to investigate the effect of sarcopenia on incident all-cause mortality in older people with T2D. Methods: Low muscle strength were set at handgrip strength <28 kg for men and <18 kg for women, and a low skeletal muscle mass index (SMI), evaluated using the impedance body composition analyzer, were set at SMI <7.0 kg/m2 for men and <5.7 kg/m2 for women. People who had both low muscle strength and low SMI were diagnosed with sarcopenia. Due to a low incidence of all-cause mortality, the propensity score was used. The propensity score was evaluated using multivariable logistic regression models with the following parameters: age, sex, duration of diabetes, history of heart disease, history of cancer, smoking, exercise, alcohol, sodium-glucose cotransporter-2 inhibitor, glucagon-like peptide-1 receptor agonist, insulin, corticosteroid, hypertension, body mass index, glycosylated hemoglobin A1c, triglycerides, and creatinine, and the C-statistic was 0.89. Results: In this prospective cohort study, 396 people with an average age and duration of diabetes of 71.3 (6.3) years and 16.3 (11.3) years, respectively, were included. Of those included, 14.6% had sarcopenia. During the average 40.5 (16.5) months of follow-up, 13 people (6 out of the 338 without sarcopenia and 7 out of the 58 with sarcopenia) died. Incident rate were 5.1/ 1000 person years of follow-up in people without sarcopenia and 41.3/ 1000 person years of follow-up in people with sarcopenia. According to Cox regression analysis, sarcopenia was associated with all-cause mortality (adjusted hazard ratio: 6.12, 95% confidence interval: 1.52–24.7, p = 0.011). Conclusion: Sarcopenia is associated with incident all-cause mortality in older outpatients with T2D.